ANALISIS BUKU TEKS BINA SEJARAH KEBUDAYAAN ISLAM KELAS IV SEKOLAH DASAR/MADRASAH IBTIDAIYAH - Ibnu Rafli, Ziba (Sindoro: Cendikia Pendidikan, 2024)
This research aims to analyze the textbook "Developing the History of Islamic Culture" for class IV Madrasah Ibtidaiyah (MI) with a focus on four main aspects: appropriateness of content, presentation, language and graphics. The research method used is literature study, which involves collecting data from related literature and in-depth analysis to evaluate books as the main learning source. The research results show that this book is relevant to the 2019 KMA Madrasah Curriculum, presenting important themes such as the preaching of the Prophet Muhammad, Hijrah, and Isra Mi'raj. The material is prepared in sufficient depth and presents accurate information in accordance with Islamic teachings. However, some complex parts require simplification to improve understanding for fourth grade students. The presentation of material supports active learning and character formation, such as the values ​​of honesty, discipline and faith. However, this book has limitations in innovative learning features, such as collaborative activities or integration of cross-disciplinary themes, as well as minimal use of technology in learning. The language used is simple, polite, and appropriate to the age level of students. An organized sentence structure and easy-to-understand vocabulary support students' independent learning process. From the readability aspect, visual settings such as typeface, font size, spacing and text layout support reading comfort. Graphic design, including the cover and layout of the book contents, is designed to be attractive and relevant to the learning theme. The included illustrations help students understand historical concepts, but the quality could still be improved to detail the context. In conclusion, this book is effective in supporting the learning of Islamic Cultural History, both in the aspects of knowledge and the formation of moral and spiritual values. To improve the quality of learning, it is recommended to enrich materials, integrate technology, and provide the latest scientific references. Keywords: book analysis, History of Islamic Culture, MI learning, KMA curriculum.